Host factors impacting the innate response in humans to the candidate adjuvants RC529 and monophosphoryl lipid A - Tiberio, Lorrie; Fletcher, Leah; Eldridge, John H; Duncan, David D (Vaccine, 2004)
The aim of this study was to determine if certain genotypes might be associated with variable responses to the candidate vaccine adjuvants RC529 and monophosphoryl lipid A (MPL), as well as to bacterial LPS, a structurally similar control stimulus. In this study, the +896 TLR4 polymorphism and selected cytokine polymorphisms were genotyped, and together with the donor sex, these factors were used to model the in vitro cytokine responses to RC529, MPL, and LPS. We show evidence that each of the three stimuli engage human TLR4, that each gave higher responses in men than women, and that TLR4 expression levels in blood monocytes were higher in men than women. From 74 to 92% of the response variation in the whole blood assay was between subjects, yet the multifactorial analyses accounted for only 3–18% of the variation within the study. Potentially there was a sex-dependent TLR4 effect since there was a significant sex-TLR4 interaction term in the multifactorial model for some responses. Since the genotypes we analyzed had such a modest impact in the study, we anticipate that +896 TLR4 genotype and the other factors analyzed in this study have only incremental effects in determining the overall response to TLR4-engaging stimuli.